2017
DOI: 10.1016/s2542-5196(17)30078-5
|View full text |Cite|
|
Sign up to set email alerts
|

Affordable house designs to improve health in rural Africa: a field study from northeastern Tanzania

Abstract: Ruth W Jensens Foundation, Copenhagen and Hanako Foundation, Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…Rather than air conditioning, this can be achieved with buildings with low thermal mass and good ventilation. 32 We observed an association between environmental temperature and child growth, but further research is needed to understand the extent to which this is mediated by food security and poverty, rather than a direct biological effect. Hotter climates are generally associated with greater levels of poverty, which is related to child growth.…”
Section: Discussionmentioning
confidence: 74%
“…Rather than air conditioning, this can be achieved with buildings with low thermal mass and good ventilation. 32 We observed an association between environmental temperature and child growth, but further research is needed to understand the extent to which this is mediated by food security and poverty, rather than a direct biological effect. Hotter climates are generally associated with greater levels of poverty, which is related to child growth.…”
Section: Discussionmentioning
confidence: 74%
“…7,8 The findings show that open eaves are the major route by which Anopheles gambiae sensu lato enters houses and that closing them or installing a ceiling below the eaves prevents a substantial proportion of the vectors from entering the living space. A pilot study 9 of modern houses in rural Tanzania showed that mosquito numbers indoors were 96% less in screened double storey buildings than outdoors, with corresponding values of 77% less in screened singlestory buildings and 23% less in traditional houses. Thus, accumulating evidence suggests that mosquito house entry can be reduced appreciably by filling or screening entry points.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, a better understanding of how disease transmitting mosquitoes move in this built environment would be illuminating. Recent experimental studies with rural African houses have demonstrated marked differences in the number of mosquitoes entering different typologies of houses (von Seidlein et al 2017, Jatta et al 2018. The reasons for the variation in mosquito-house entry is due to the human odours that leak from a building and the porosity of the structure.…”
Section: Basic Research On Vectors and The Built Environmentmentioning
confidence: 99%